Geological heritage and sustainable development in Santiago Island (Cape Verde) - Pereira, J. M. (2005)
This work about the national geological heritage is the very first study ever made in Cape Verde. For logistical reasons the work is limited to the Santiago Island in spite of the intentions to extend the same methodology to all islands. The methodology was based on the following steps: i) inventory of geosites; ii) geological characterisation; iii) assessment of the vulnerability and relevance.